1969
DOI: 10.1128/jb.100.1.445-452.1969
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Occurring Bacterial Transformations in Mice

Abstract: In 1963, it was reported that deoxyribonucleic acid (DNA)-mediated transformations could take place spontaneously between genetically distinguishable pneumococci growing in a living host, the mouse. It was found in the present study that such transformations could be increased in frequency if infected animals were treated with a drug which kills only one of the two infecting strains. The frequency of in vivo transformations w4s also increased if the infection was prolonged. Interspecific transformation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
(22 reference statements)
2
10
0
Order By: Relevance
“…The frequency of transformation in the murine lung varied with different pneumococcal strains, as previously observed in the peritoneal cavity (19). Transformation of CD-VII-Smr, for example, was more common than transformation of IIIS-1R6.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The frequency of transformation in the murine lung varied with different pneumococcal strains, as previously observed in the peritoneal cavity (19). Transformation of CD-VII-Smr, for example, was more common than transformation of IIIS-1R6.…”
Section: Resultssupporting
confidence: 62%
“…Although intraperitoneal transformations between strains R36NCSmr and IIIS-1R6 have been reported in mice (4,18,19), we detected such a transformation in the doubly infected lungs of only 1 mouse among 117 injected with ethanol and 91 injected with saline (see Discussion). In contrast to the observations of Conant and Sawyer (4), no transformants were isolated from the blood.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…As his approach involves the use of large amounts of heat-killed donors, it relies on artificial conditions and is not useful as a method for studying gene transfer in vivo. However, a few pioneering studies from the 1960s have demonstrated the occurrence of transformation during mixed pneumococcal infection in mice and man (Ottolenghi & MacLeod, 1963;Conant & Sawyer, 1967;Ottolenghi-Nightingale, 1969, 1972. In mice, transformation was shown to take place even when living donor and recipient cells were injected at different sites or 6 h apart.…”
Section: Discussionmentioning
confidence: 99%
“…Under natural conditions pneumococcus might participate in gene exchange when located in biofilms in places such as the nasopharynx, the common carrier state of this microorganism [46,106]. In fact, there are data supporting the idea that DNA‐mediated spontaneous transformations may occur in nature, even interspecific transformation between pneumococci and streptococci, and that they may play a role in bacterial infections [127,128]. Interestingly, type 9 pneumococci were transformed by DNA released from living unencapsulated pneumococci sprayed onto the pharynx in a healthy human carrier [128].…”
Section: Cell Wall Hydrolasesmentioning
confidence: 99%